Introducción del control interno bajo el modelo coso en una pyme para el aseguramiento de la información en el cumplimento de las normas. (2023)
It is important to recognize the failures or errors that may occur in one or more procedures, these affect the normal development and growth of SMEs, as well as affect its competitive in the market in which it influences, now through this article we will see how a small organization can enter to design and implement an effective COSO model to establish a control, evaluate the risks, the fulfillment of the norms and the regulations of internal policies of the company.